The effect of personal selling on product purchase decision in Sibolang Durian - Jenni Tarigan (JURNAL GLOBAL MANAJEMEN, 2021)
This research was conducted to determine the effect of personal selling on product purchasing decisions partially at Sibolang Durian Business, Medan. The sample used simple random sampling which directly selected 38 consumers. This type of research uses quantitative research with a causal associative research approach by using questionnaires which are considered appropriate to the research conducted which aims to determine the causal relationship between the independent variable (influencing variable) and the dependent variable (influenced variable). In this study, using validity and reliability and normality testing and using data analysis techniques, namely multiple linear regression analysis with the help of SPSS 20 software. t test), namely t count (2.229)> t table (1.688) with a significance value <0.05. This means that the personal selling hypothesis H1 is accepted and H0 is rejected. So it can be concluded that sales through personal selling marketing means carried out by the Sibolang Durian business also have an influence on consumer decision making in buying Sibolang Durian products.